Influence of the maturation stage on the physical-chemical quality of fruits of umbu (Spondias tuberosa) - de Menezes, Pedro Henrique Santos (2017)
Harvesting at suitable maturation stages is determinant in maintaining post-harvest quality of umbu fruit. In this sense, the aim of this work was to determine the influence of the maturation stage on the physical-chemical quality of umbu fruits from the brazilian northeast. The experiment was conducted at the Food Technology Laboratory of the Agrarian Sciences Center of the Federal University of Roraima, Boa Vista, Roraima, Brazil. The experimental design was a completely randomized design with ten replicates and one fruit per experimental unit. The treatments consisted of three maturation stages of the fruits: green, once and ripe. The physical characteristics evaluated were: fruit length, fruit diameter, seed mass, bark mass, pulp mass, total mass and pulp yield. The determination of the chemical quality was evaluated: pH, soluble solids content, titratable acidity and soluble solids / titratable acidity ratio. It was concluded that the stages of maturation of umbu fruits exert different response capacities regarding their biometry. Fruits of umbu in the green stage have higher mass and consequently higher yield of pulp. The fruit quality of umbu is not influenced by the different maturation stages of the fruits.